PENINGKATAN KEPUTUSAN PEMBELIAN MELALUI KUALITAS PRODUK, CITRA MEREK DAN KESADARAN MEREKSMARTPHONE SAMSUNG PADA MAHASISWA UNIVERSITAS STIKUBANK SEMARANG - Kasmari Kasmari; Lie Liana; Kis Indriyaningrum; Aisyah Sarania (Jurnal Ilmiah Dinamika Teknik, 2019)
This study aims to examine the improvement in product quality, brand image, and brand awareness of the purchasing decisions of Samsung smartphones. The population was drawn from Unisbank students using Samsung-brand smartphones, and a sample of 99 students. The sampling technique is proportionate random sampling. The data used in this study are primary data, with questionnaires as research instruments. While the research instruments include validity test, reliability test, multiple linear regression, F test, coefficient of determination test (R²), and t test (hypothesis). The results of data processing show that product quality has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and brand awareness has no positive and significant effect on purchasing decisions.